2020
DOI: 10.3390/antiox9050449
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Euonymus alatus Extract on Scopolamine-Induced Memory Deficits in Mice

Abstract: Euonymus alatus is considered to elicit various beneficial effects against cancer, hyperglycemia, menstrual discomfort, diabetic complications, and detoxification. The young leaves of this plant are exploited as food and also utilized for traditional medicine in East Asian countries, including Korea and China. Our preliminary study demonstrated that ethanolic extract from the Euonymus alatus leaf (EAE) exhibited the strongest antioxidant enzyme-inducing activity among more than 100 kinds of edible tree leaf ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Besides the behavioral impairment, Sco-induced amnesic zebrafish could mimic the oxidative stress event of AD development, although its exact oxidative damage mechanism is uncertain [ 39 ]. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that activates the pathways of endogenous antioxidant defense and the production of the antioxidant enzymes [ 4 , 40 ]. Kanninen et al [ 41 ] showed that attenuation of the Nrf2-ARE pathway coincided with disease progression in APdE9 transgenic mice modeling AD.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the behavioral impairment, Sco-induced amnesic zebrafish could mimic the oxidative stress event of AD development, although its exact oxidative damage mechanism is uncertain [ 39 ]. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that activates the pathways of endogenous antioxidant defense and the production of the antioxidant enzymes [ 4 , 40 ]. Kanninen et al [ 41 ] showed that attenuation of the Nrf2-ARE pathway coincided with disease progression in APdE9 transgenic mice modeling AD.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was collected to estimate the antioxidative ability. MDA, a marker of lipid peroxidation, was detected following the thiobarbituric acid method [ 27 ]. The GSH level was detected using the dithiodinitrobenzoic acid method, SOD activity was assayed using the xanthine oxidase method, and T-AOC was determined using the colorimetric method, and all indexes were detected following the manufacturer’s protocols [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The seeds and stems of some spindle species are a source of biologically active substances such as diterpenes, triterpenes, sesquiterpenes, cardiac glycosides, lectins, alkaloids and squalene 17 21 . Tinctures made of spindle seeds have antioxidant, antibacterial and insecticidal properties, and they are used for detoxification and in the treatment of cancer, hyperglycemia, menstrual discomfort, diabetic complications, and dermatological diseases 16 , 17 , 21 23 .…”
Section: Introductionmentioning
confidence: 99%